Parenthood is a fiduciary relationship - Smith, Lionel (University of Toronto Law Journal, 2020)
Canadian courts have held that parents stand in a fiduciary relationship with their children. Some commentators take the view that this is an inappropriate and unwarranted extension of a set of concepts that were originally elaborated in the context of the management of property rights and other pecuniary interests. The goal of this article is to assess the characterization of parents as fiduciaries in the light of recent scholarship on fiduciary law. I argue that, while there are significant differences between the parent-child context and more established fiduciary categories, the characterization of the parent as a fiduciary toward his or her child nonetheless captures a central – indeed, a defining – element of the parent-child relationship, which is also a characteristic element of all established fiduciary relationships: namely, the possession of legal powers that are held in a managerial or other-regarding capacity for the benefit of another person. Every aspect of the traditional property-based fiduciary relationship finds its counterpart in the juridical relationship between a parent and his or her minor child. The ability of a parent to take account of his or her own interests in relation to some exercises of the parent’s decision-making powers is also found in many established fiduciary relationships. The recognition of parenthood as a fiduciary relationship leads to a better understanding of fiduciary relationships because it clarifies how such relationships are constituted, and it clarifies that they extend to any situation where one person is empowered and authorized to look after the interests of another, whether those interests be financial or entirely personal.